2009
DOI: 10.1016/j.jneb.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Fruits and Vegetables at Home: Child and Parent Perceptions

Abstract: Objective Examine child and parent perceptions of home food environment factors and associations with child fruit and vegetable (FV) intake Design Research staff administered surveys to children during after-school sessions and parents completed surveys by mail or over the phone Setting Four urban elementary schools in St. Paul, Minnesota, serving primarily low-income populations Participants 73 children (55 girls, 18 boys) participating in a theater-based intervention aimed at obesity prevention and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
42
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 23 publications
6
42
2
Order By: Relevance
“…Family food culture was associated with FV intake, consistent with the literature that shows that increased family meals, the main component of family food culture, is associated with increased FV intake in children [7679]. This was the only significant variable in the FV intake model and also the only child-reported social support; other studies have also found that various types of parental support reported by children were more associated with children’s FV intake than the parent’s perceptions of that same support [8082]. …”
Section: Discussionsupporting
confidence: 88%
“…Family food culture was associated with FV intake, consistent with the literature that shows that increased family meals, the main component of family food culture, is associated with increased FV intake in children [7679]. This was the only significant variable in the FV intake model and also the only child-reported social support; other studies have also found that various types of parental support reported by children were more associated with children’s FV intake than the parent’s perceptions of that same support [8082]. …”
Section: Discussionsupporting
confidence: 88%
“…A potential explanation for this is that family meals provide an opportunity for parents to be positive role models to their children (7) and to talk about healthy eating. In contrast to findings from other studies (8,18) we did not observe any association between FV intake and parental support, including encouragement, parents consuming FV and buying FV. This might reflect the overall parenting style and inappropriate food-related parental practices within the Cypriot context.…”
Section: Discussioncontrasting
confidence: 99%
“…Parental nutritional habits have been consistently correlated with healthy dietary behaviours 44. The relationship between parental intake and child's intake can be explained through modelling, and the child's simple desire to imitate their parents 17 29 30 45. Increased availability would increase children's familiarisation with different fruits and vegetables, which is considered to be a key determinant in children's consumption 42 46 47.…”
Section: Discussionmentioning
confidence: 99%